Kinerja Perusahaan dan Nilai Perusahaan Sektor Infrastruktur Indonesia - Andriyani, Karimah; Fatihah Nida 'Ul Chasanah (Journal Of Islamic Economics And Finance, 2024)
This study aims to determine the effect of firm size, liquidity and capital structure on firm value in infrastructure sector companies listed on the Indonesian Sharia Stock Index for the period 2017-2021. This study uses quantitative research methods with sampling techniques using purposive sampling. This study used 80 research samples. The type of data used is secondary data in the form of annual financial reports of infrastructure sector companies listed on the Indonesian Sharia Stock Index in 2017-2021 which can be accessed through the website of each company. The data obtained is then processed using SPSS 26. The analysis used is the classical assumption test, multiple linear regression analysis, t test, F test and coefficient of determination. The results of this study indicate that firm size has a negative and significant effect on firm value with a t value of -4.131 and a sig value 0.000, liquidity has a negative and significant effect on firm value with a t value of -2.507 and sig value 0.014, while capital structure has no effect and is insignificant to the firm value with t value 0.715 and sig value 0.477. Simultaneously firm size, liquidity and capital structure affect firm value with an F value of 6.962 and a sig value 0.000. From the results of the coefficient of determination, a value of 0.185 is obtained, which means that firm size, liquidity and capital structure have the ability to influence firm value by 18.5%.